2009
DOI: 10.1007/s11103-009-9552-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher accumulation of F1-V fusion recombinant protein in plants after induction of protein body formation

Abstract: Improving foreign protein accumulation is crucial for enhancing the commercial success of plant-based production systems since product yields have a major influence on process economics. Cereal grain evolved to store large amounts of proteins in tightly organized aggregates. In maize, gamma-Zein is the major storage protein synthesized by the rough endoplasmic reticulum (ER) and stored in specialized organelles called protein bodies (PB). Zera (gamma-Zein ER-accumulating domain) is the N-terminal proline-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Previous work demonstrated that the proline-rich N-terminal domain of ␥-zein (Zera) fused to a protein induced PB formation in plant vegetative tissues (24,25,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that the proline-rich N-terminal domain of ␥-zein (Zera) fused to a protein induced PB formation in plant vegetative tissues (24,25,47).…”
Section: Discussionmentioning
confidence: 99%
“…The Zera® domain, (N-terminal proline-rich domain: γZein ER-accumulating domain) of maize Zein gene is able to form PB bodies. This domain, in addition to other constituents, led to a threefold increase in the Yersinia pestis F1-V antigen fusion protein accumulation when using the fusion construct, in comparison to the construct lacking it, in three separate transient or stable transformation systems in Nicotiana benthamiana, Medicago sativa (alfalfa) and Nicotiana tabacum NT1 cells (Alvarez et al, 2010). To facilitate the removal of these tags after purification, the recognition sequence of the protease TEV (the sequence Glu-Asn-Leu-Tyr-Phe-Gln-(Gly/Ser)(ENLYFQ(G/S)) can be added between the protein of interest and the tag (Kapust & Waugh, 2000;Tropea, Cherry, & Waugh, 2009;Waugh, 2011).…”
Section: Fusion Tags In Plant Molecular Pharmingmentioning
confidence: 98%
“…However, the small tags in plant molecular pharming are characterized by their ineffectiveness, lack of scalability and high cost (Joensuu et al, 2010;Waugh, 2005). Some fusion tags have increasingly been gaining more attention as a new, effective way of facilitating the expression, extraction and purification of pharmaceutical proteins, such as hydrophobin (Joensuu et al, 2010;Joensuu, Conley, Linder, & Menassa, 2012), zein domain (Alvarez, Topal, Martin, & Cardineau, 2010), elastin-like polypeptides (Conley, Joensuu, Richman, & Menassa, 2011;Floss et al, 2009) and soybean agglutinin (SBA). The SBA affinity tag is an effective system which can be used for quick and efficient purification of recombinant proteins (Tremblay, et al 2011).…”
Section: Fusion Tags In Plant Molecular Pharmingmentioning
confidence: 99%
“…44,45 A fusion protein comprising Yersinia pestis antigen F1-V and the proline-rich domain of γ-zein accumulates to threefold the levels of the F1-V antigen alone, through the induction of heterologous protein bodies. 43 The Spanish company ERA Biotech has commercialized this platform as Zera ® technology for the large-scale production of pharmaceutical proteins in plants.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…42 An approach to achieve both goals at the same time is the induction of recombinant protein bodies containing the vaccine antigen. 43 Protein bodies are organelles derived from the ER; they occur naturally in seeds and are used to stockpile storage proteins. Evidence suggests that the storage proteins themselves contain structures that induce proteinbody formation: the proline-rich N-terminal domain of γ-zein, can induce protein bodies in cells that normally do not contain such co-accumulate with oleosin, allowing enrichment of the recombinant protein in the oil body fraction, which can be separated easily.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%